Impact of intervention on preanalytical errors assessed by six sigma and Pareto’s principle - Sweta Kulkarni; S. Vinothini; Wilma Delphine Silvia CR (Al Ameen Journal of Medical Sciences)
Introduction: Preanalytical steps are the major sources of error in the clinical laboratory. The analytical errors can be corrected by quality control procedures but there is a need for stringent quality checks in the preanalytical area as these processes are done outside the laboratory. Sigma value depicts the performance of the laboratory and its quality measures. Hence in the present study, six sigma and Pareto principle were applied to preanalytical quality indicators to evaluate the impact of the intervention. Materials and Methods: The present analytical interventional study was conducted in a tertiary care hospital after obtaining Institute’s ethical waiver. A total of 31,003 samples before intervention and 31,114 samples after intervention were screened for preanalytical errors in sample collection like Hemolysed, clotted, inadequate sample, Lipemic from clinical biochemistry section over a period of one year. Six sigma values were calculated using the Westgard online formula. Results: The clotted and inadequate samples were the major preanalytical errors with a sigma value of 3.5 and after intervention sigma value was 4.6 and 4.7 respectively. The Pareto`s chart (80/20 rule) also depicted the same results. Conclusion: The interventions like training and providing standard operating procedures to laboratory technicians and nursing staff reduces the frequency of preanalytical errors and improves the sigma value.